Fishing vacation - Wong, Shin Lan; Chen, Rabbit (Kuala Lumpur : TBS Productions [production company] ; VTR Distributors [distributor])
City life is very hectic and stressful. If given a holiday, how would you spend it to reduce the stress and tension? To relax and rest their mind, our few friends choose a place where there is fresh air, natural surrounding and most importantly a satisfying fishing trip. In this special fishing vacation episode at the beautiful and captivating, Terengganu's Kenyir Lake in the east coast of Malaysia, you will experience a spectacular battling between man and fish. In this succesful fishing adventure the anglers was rewarded with various types of fishes caught - Sebarau, Grey Featherback (Belida), Giant Snakehead (Toman), Catfish (baung), Striped Catfish (Patin), Marble Goby (Ketutu) and etc.
Executive producer, Chen Puie Heng ; script, Rabbit Cheng, Jennifer Chen ; editor, Brian Loke, Wong Kim Fatt
Chinese narrator : Chen Puie Kong, Lai Yeng Kheng
Malay narrator : Neubert Ambrose
Keywords: Fishing; Fishing -- Equipment and supplies